High level of serum hepcidin in the group of juniors training canoeing - preliminary report - Justyna Przybyszewska; Michał Gośliński; Oliwia Rolirad; Andrzej Rakowski (Kazimierz Wielki University, 2018)
Introduction The results of biological and clinical studies available in the literature indicate a relationship between physical effort and iron deficiency with coexisting microcytic anemia (iron deficiency anemia) or without anemia (IDNA; iron depletion without anemia). Currently, due to unfavourable clinical consequences for athletes, both IDA and IDNA, i.e. reduced endurance and reduced energy efficiency, intensive research is underway to determine the mechanism of these disorders. In the light of recent studies on biological activity of hepcidin, it is believed that hepcidin can play an important role in the pathogenesis of syderopenia in athletes. Therefore, the aim of the study was to assess the hepcidin concentration against the background of iron management parameters in young junior team members training canoeing in high-performance kayaking. Objective The aim of this study was to evaluate the concentration of serum hepcidin and selected blood morphology parameters in the group of junior canoeists. Material and methods The study group consisted of 29 young athletes (20 boys and 9 girls) participating in a training camp at the Central Sports Centre in Wałcz. The average age of participants of both boys and girls was 16.5 ± 0.6 years. Results Results of this study showed that the average hepcidin concentration in the study group was higher than that observed by other authors for healthy peers. In addition, in 8 juniors (including 6 boys and 2 girls), the hepcidin concentration was above the adult reference range. There was no statistically significant difference in hepcidin concentration between boys and girls. However, a wide range of individual hepcidin values was observed in both groups. In addition, ferritin levels were below normal with 8 patients. A positive correlation between hepcidin and ferritin has been shown. Conclusion The results obtained in the study indicate the hepcidin could be a major contributor to poor iron status observed in the athlete trains professionally. Our research suggests it is necessary to monitor the diet of young athletes with respect to iron content and its proper bioavailability.